Забезпечення студентоцентрованого підходу у закладах вищої освіти - Гладких, Ганна Валеріївна; Гладких, Анна Валерьевна; Hladkykh, Hanna (My University, 2020)
UK: У статті висвітлюються основні переваги студентоцентрованого підходу у закладі вищої освіти, розглядаються механізми та інструменти забезпечення студентоцентрованого підходу. Наголошується на необхідності забезпечення спільної роботи здобувачів вищої освіти, викладачів та адміністрації, використання інформаційно-комунікаційних технологій та компетентнісного підходу для підготовки майбутніх фахівців. EN: In the article the main advantages of the student-centered approach in higher education institutions are highlighted, the mechanisms and tools of a student-centered approach ensuring are discussed. It is emphasised on the need to ensure the joint effort between higher education seekers, teachers and administration, the use of information and communication technologies and a competency-based approach to future specialists training.
Providing a Student-centered Approach in Higher Education Institutions
Keywords: компетентнісний підхід; студентоцентрований підхід; студент; заклад вищої освіти; student-centered approach; competency-based approach; student; higher education institution